Marmara University Medical Students' Perception on Sexual Violence against Women and Induced Abortion in Turkey - (:unkn) unknown (My University, 2016)
0

Background: Historically, sexual assault is a common issue in Turkey. As doctors are one of the steps to help sexually assaulted women, medical students should have basic knowledge of and sensitivity regarding this subject. Another common women's public health issue is induced abortion. In countries where access to abortion is restricted, there is a tendency towards unhealthy abortion. Aims: The aims of this study are: (1) to determine the attitudes and opinions of Marmara University Medical Faculty students about sexual assault against women and induced abortion and (2) to propose an educational program for medical students about sexual assault and abortion. Study Design: Cross-sectional study. Methods: The questionnaires were self-administered and the data were analyzed using SPSS v.15.0. First, the descriptive statistics were analyzed, followed by Chisquare for contingency tests assessing differences in attitudes toward sexual assault and induced abortion by factors such as gender and educational term. Differences were considered statistically significant at p<0.05. Results: About 89.6% of the participants (n=266) reported that they had never been sexually assaulted and about 11.5% of the women (n=19) had been sexually assaulted. There was no significant relationship between previous sexual assault and gender (p>0.05). Although there was no significant difference regarding the extent of punishment by victim's status as a virgin, 21.3% (n=63) agreed that punishment should be more severe when the victim was a virgin. About 40.7% (n=120) agreed that the legal period of abortion in Turkey (10 weeks) should be longer. The majority (86.1%, n=255) agreed that legally prohibiting abortions causes an increase in unhealthy abortions. Conclusion: An educational program on these issues should be developed for medical students.
Keywords: Cerrahi